E-Commerce Road Map and Equal Digital Opportunity in Indonesia - Sartika Lestari (Universitas Negeri Semarang, 2025)
Understanding the program's impact on digital capability growth is considered necessary to support progress in digital inclusion through measured evaluation. This study seeks to understand the influence of regulation on the level of digital opportunity and its growth in Indonesia. Utilizing a descriptive-comparative analysis with the Digital Opportunity Index framework, this study measures digital opportunity through e-commerce among Small and Medium Enterprises across 34 provinces. The results show that while the DOI score at the national level remained stagnant, 21 provinces experienced growth, 12 provinces experienced negative growth, and 1 province remained unchanged. Furthermore, in the opportunity category, 26 provinces and the national level experienced growth, while the other 8 provinces experienced zero growth. The infrastructure category showed that 6 provinces experienced growth, 27 provinces and the national level presented negative growth, and 1 province showed zero growth. The utilization category showed that 33 provinces and the national level experienced positive growth, leaving only one province with negative growth. This research suggests that, to provide continuous support for digital development, the government and related institutions should consider regulations or programs that promote infrastructure development, ensuring it is available and affordable at the provincial level.